2010
DOI: 10.3109/15376510903572631
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and gene expression analysis of mice exposed to diethylstilbestrol

Abstract: The estrogenic compound diethylstilbestrol (DES) has been widely studied to understand its potential involvement in endocrine function and carcinogenesis. This study examined the influence of DES on adult mice by histopathological analysis and studied the gene expression changes using mRNA differential display. Pathological changes in the mice following DES exposure included testicular atrophy, ovarian and hepatic fibrosis, and reduced numbers of mature oocytes and spermatogenic cells. Other pathological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Accordingly, GSI of these fish were found to be significantly reduced at 4 months of age, proving that the exposure to DES during early stages of development had a long-lasting effect on germ cell proliferation in XX females. A recent report from mouse showed that exposure to DES reduced number of oocytes and spermatogenic cells (26). Previously, also neonatal exposure to DES has been shown to reduce the number of germ and Sertoli cells in testes of rats and mouse (27,28), implying that the signaling pathway that is affected by DES could be well conserved across the species.…”
Section: Figmentioning
confidence: 99%
“…Accordingly, GSI of these fish were found to be significantly reduced at 4 months of age, proving that the exposure to DES during early stages of development had a long-lasting effect on germ cell proliferation in XX females. A recent report from mouse showed that exposure to DES reduced number of oocytes and spermatogenic cells (26). Previously, also neonatal exposure to DES has been shown to reduce the number of germ and Sertoli cells in testes of rats and mouse (27,28), implying that the signaling pathway that is affected by DES could be well conserved across the species.…”
Section: Figmentioning
confidence: 99%
“…Hong et al (2010) demonstrated effects of DES on gene expression, but did not provide insight into the injurious effects, or lack thereof, on male fertility. Three other studies revealed a statistically insignificant relationship, or a complete lack of correlation.…”
Section: Resultsmentioning
confidence: 98%
“…For example, Vitamin A has been linked with re-establishing sperm motility and decreasing the number of malformed sperm following neonatal exposure to BPA (Hendry et al, 2006). Likewise, the use of ginkgo biloba as a possible therapeutic agent for testicular injury caused by DES exposure is currently being studied (Hong et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations